Cancer Statistics and Anticancer Potential of Peganum harmala Alkaloids: A Review - Tohfa Nasibova (Borneo Journal of Pharmacy, 2022)
Cancer is one of the most common diseases in the world. Although it develops in various organs and tissues, some species maintain a stable position in the ranking. Although the cancer causes are different, the specific grounds for each type are also noted. Sometimes the increase in incidents and mortality is associated with geographical reasons. Increases in statistics, expensive and chemotherapeutic methods focus on plant-based substances. One of such potential plants is Peganum harmala, which contains alkaloids such as harmine, harmaline, harmol, and harmalol. The effects of these compounds on many cancer cells have been tested, and positive results have been obtained. This fact reinforces the claim that more in-depth research on noted alkaloids is needed.